Cultivation of Ecological Consciousness for a Sustainable Agroecosystem - Gangwar, Dheerendra Singh (Journal of International Buddhist Studies, 2020)
During the last few decades, it is observed that the economics and the ecology of the farming landscapes are not moving in the right direction. Farmers are facing many challenges as the cost of food production is escalating but crops are not sold at profitable prices. Even capital intensive chemical farming has a role in environmental degradation and adversely affected human health. These issues are identified as the root cause of various social and ecological problems. In such circumstances, cultivation of ecological consciousness based upon the basic principles of socio-ecological sustainability is emerging as the greatest need of the hour. The middle way path of lord Buddha illustrates the psycho-spiritual perspective of environmental conservation, sustainable development, and peaceful co-existence. It emphasizes community-driven mechanisms for inclusive dialogue, contemplation, meditation, and conflict prevention. With the help of a case study, this work highlights the role of Anupashyana Farming in ensuring the socio-economic well-being of participating farmers. It is an integrated farming approach that combines Buddhist ecological values, principles of Buddhist Economics, the role of social capital in rural transformation, and digital agriculture services.